Effects of Zataria multiflora Extract and Carvacrol on Doxorubicin-Induced Oxidative Stress in Rat Brain - Reza Mohebbati; Mohammad Jalili-Nik; Maryam Paseban; Mohammad Naser Shafei; Abolfazl Khajavirad Rad (Tabriz University of Medical Sciences, 2018)
Background: Due to the antioxidant effects of Zataria multiflora (ZM) and Carvacrol (CAR) in various problems and the prominent role of the ROS in neurotoxicity induced by Doxorubicin (DOX), this study was designed to investigate the effects of ZM hydroalcoholic extract and CAR on DOX-induced oxidative stress in rat brain. Methods: 24 male rats were randomly divided into four groups including: 1)Control ,2)Doxorubicin (DOX) that received DOX via a tail vein on the first day of the study, 3,4) ZM+DOX and CAR+DOX which received ZM and CAR by gavage for 28 consecutive days. Brain tissue removed for redox markers evaluation. Results: MDA level in the DOX group was significantly increased compared to control group while in treated groups did not show any significant changes in comparison with the DOX group. Also, Thiol content in DOX group showed significant reduction compared to control group. Thiol contents in treated groups showed no significant difference compared to DOX group. Catalase (CAT) activity, an antioxidant enzyme, in the DOX group were significantly decreased compared to control group and increased in treated rats in comparison with the DOX group. Activity of Superoxide dismutase (SOD), an antioxidant enzyme, in the DOX group was significantly reduced compared to control group and increased in treated rats in comparison with the DOX group. Conclusion: The present study showed that ZM hydroalcoholic extract and CAR could inhibit DOX induced oxidative stress of the brain mainly with effect on the enzymatic antioxidant defense system.